The results of agro-ecological monitoriThe results of agro-ecological monitoring of rangelands - Nasiyev, B. (Вестник государственного университета имени Шакарима. - 2020, 2020)
The article discusses the results of research on the degradation of vegetation cover of forage lands in the semidesert zone. As shown by geobotanical research data, a clear predominance of vegetation degradation over other processes of desertification is characteristic of forage lands in the Bokeyurdinsky and Zhangalinsky districts of the West Kazakhstan region. The analysis of materials obtained in the course of scientific research on the territories of forage lands in the semi-desert zone of Western Kazakhstan allowed us to distinguish 3 classes of desertification by degradation of vegetation cover. In zhangali district, vegetation and soil cover of pastures of Zhanakazan rural district are most degraded; in the rest of The territory, degradation has 1 and 2 degrees
Keywords: зко; кормопроизводство; деградация; растительность; продуктивность; пастбища; опустынивания; degradation; vegetation; productivity; pastures; desertification; отечественное издание; научный журнал; периодическое издание; журнал коксон